Sportbedingte Schäden der Wirbelsäule und Empfehlungen zum Training - Schönle, C. (Sport-Orthopädie - Sport-Traumatologie, 2002)
Studies show an increased risk for typical spine damages during intensive sport. A healthy spine normally is not damaged when participating even in high performance sport, but if deviations, dysplasia or diseases are present, sports specific damages can occur. The positive or negative effects of sports activities on the spine are discussed and guidelines for a healthy way for going in sport are given. If there are degenerative or other changes of the spine the sportsman must be advised which kind of sport is appropriate.